Depressive symptoms in pregnant women with high trait and state anxiety during pregnancy and postpartum - Chinchilla-Ochoa, Daniela (Int J Womens Health, 2019)
Background: Depression and anxiety are frequent during pregnancy, and epidemiological studies demonstrate high rates of co-morbidity. Aims: To evaluate the association between the trait and state anxiety and depressive symptoms in women during the perinatal period. Method: A transversal study was conducted at the National Institute of Perinatology (INPer, Mexico City) from 2012 and 2015. Pregnant women diagnosed with Major Depressive Disorder (MDD) were included (N=128). Depressive and anxiety symptoms were evaluated using CES-D and STAI, respectively. Patients were sub-classified according to percentile 75 for Low and High Trait Anxiety (LTA, HTA) and Low and High State Anxiety (LSA, HSA); depressive symptoms were compared between pregnant women and women in the postpartum, by state and trait levels. Results: CES-D scores differed according to state and trait anxiety levels: while we observed that depressive scores (CES-D) were higher in HTA patients compared to LTA prenatally (35.9±9,5 vs 21.2±10,8 respectively; p=0.001), this finding was not observed in the postpartum period. In the case of state anxiety depressive scores were elevated among HSA versus LSA groups before delivery (33.0±11.3 vs 14.0±6.7 respectively; p=0.008) and after partum (35.1±8.06 vs 10.0±6.0; p=0.005). Conclusions: Patients showed higher scores of depressive symptoms when high trait or state anxiety comorbidity is present during the perinatal period. In the postpartum period, even low trait anxiety scores were associated with high depressive scores.